Development of the community initiatives Urban and Urban II in the deprived peripherial areas of the Spanish towns. A contribution to the urban regeneration practice in Spain (Ciudades, 2017)
Since 1990, when the EEC published the «Green Paper on the Urban Environment», the European Union has carried out an active role fighting against the decline that affects the European cities, through contributions that have consisted of recommendations, guidelines and a direct action on the deprived urban areas financed through the Cohesion Fund, the ERDF and the ESF. This task has led to the definition of a specific instrument to fight against urban decline in 1994: the URBAN Community Initiative. In Spain, the urban dimension of the EU policy and particularly URBAN and URBAN II have supposed a relevant contribution to the revitalization of the neighbourhoods in crisis. This article addresses the question of how and to what extent the influence of URBAN has transformed the urban regeneration practice in the peripheral areas of the country.
Keywords: urban revitalization; URBAN Community Initiative; peripherial area; integral approach; participation; collaborative policy